Recreational Tourism in the World and Its Perspectives in Uzbekistan - Khamidova Nazokat; Turdiyeva Nargiza Mardonovna (Indonesian Journal of Cultural and Community Development, 2020)
The aim of this article is to broaden the capacity of Uzbek Recreational Places with the example of Zaamin Sanatorium, providing suggestions to boost this place's competitiveness in recreation. The numerous forms of health tourism are gaining an enhanced presence in world tourism these days and this is also true of some countries' economic success. Health tourism with ongoing development over the past decade has seen a dynamic development, primarily in the area of wellness tourism at both national and international levels. Consequently, the advance of health tourism is given significant importance in developing countries. This form of tourism is considered one of the spheres of great importance to which the population pays attention. Health tourism encourages both the prevention of physical and emotional exhaustion and the treatment of many chronic illnesses. For this reason, for a more productive and healthy vacation, tourists go to resort areas, which are the main component of the medical health tourism. Medical tourism on a global scale is one of the most dynamically developing types of tourism. So, according to the forecast of the World Health Organization Conservation Agency (WHO), by 2022 tourism together with the healthcare sector will become one of the most priority areas for the development of national economies. In this article advantages of health and recreational tourism, the ways of providing this service in different countries, recreational facilities, infrastructure and resource of Uzbekistan are going to be represented. Besides that, some problems in local recreational tourism with the example of “Zaamin” Sanatorium in Jizzakh region of Uzbekistan based on the personal communication are going to be expended.